2018
DOI: 10.1159/000487569
|View full text |Cite
|
Sign up to set email alerts
|

Knockout of Low Molecular Weight FGF2 Attenuates Atherosclerosis by Reducing Macrophage Infiltration and Oxidative Stress in Mice

Abstract: Background/Aims: Fibroblast growth factor 2 (FGF2) plays a predominant role during angiogenesis in the adventitia and in atherosclerotic plaque. A dilemma exists, however, as to whether angiogenic stimulation by FGF2 for the prevention and treatment of atherogenesis is feasible. The aim of this study is to investigate the effect of the 18-kDa FGF-2 isoform on atherosclerosis progression in high-fat diet-fed apolipoprotein E knockout (ApoE-/-) mice. Methods: We established a model of atherosclerosis using ApoE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…Similarly, Liang et al, 2018 showed that knockout of FGF2 reduced infiltration and accumulation of macrophages at different stages of atherosclerosis. They also showed that the knockout induced a reduction in CCL-2 and VCAM-1 expression in the atherosclerotic plaques 6 . Therefore the observed reduced macrophages content in the ApoE3*Leiden mice treated with K5 could be either due to the reduced number of circulating monocytes or a reduced monocyte infiltration in the lesion probably due to a reduced CCL-2 and VCAM-1 expression or a combination of both processes.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Similarly, Liang et al, 2018 showed that knockout of FGF2 reduced infiltration and accumulation of macrophages at different stages of atherosclerosis. They also showed that the knockout induced a reduction in CCL-2 and VCAM-1 expression in the atherosclerotic plaques 6 . Therefore the observed reduced macrophages content in the ApoE3*Leiden mice treated with K5 could be either due to the reduced number of circulating monocytes or a reduced monocyte infiltration in the lesion probably due to a reduced CCL-2 and VCAM-1 expression or a combination of both processes.…”
Section: Discussionmentioning
confidence: 98%
“…Basic fibroblast growth factor (bFGF) is involved in the pathogenesis of atherosclerosis 3 and especially in the regulation of processes that drive plaque instability 4,5 . It is a known regulator of angiogenesis, macrophage infiltration as well as smooth muscle cells (SMCs) fate 6,7 . A member of the fibroblast growth factors family, bFGF is secreted by SMCs and macrophages 8,9 and exerts its activities by binding to one of the four FGF receptors (FGFR1-4) on the cell surface of different cell types, among which endothelial cells (ECs) and SMCs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, overexpression of FGF‐2 LMW increases bone mass by enhanced osteoblast activity (Xiao et al., ). Apart from its positive effects on bone maintenance, FGF‐2 LMW was also reported to promote inflammation and support oxidative stress in atherosclerosis (Liang, Wang, Ma, Yan, & Yang, ). Interestingly FGF‐2 HMW has been shown to co‐localize with survival of motor neuron protein (SMN), a mutated protein in patients suffering from the neuromuscular disease spinal muscular atrophy (SMA; Claus et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…FGF-2 also has several isoforms resulting from alternative initiations of mRNA translation, with isoform-selective biological activities: a 17 KDa cytoplasmic isoform and two higher molecular weight isoforms: 21 and 23 KDa (Liu et al, 2015;Meo Burt et al, 2016;Wang et al, 2018; Figure 1A). The structure of 17 KDa FGF-2 has been determined by several groups, and the backbone of FGF-2 has a trigonal pyramidal structure with 12 antiparallel beta-sheets, and helix-like structures have been found at residues 131-136 (Liao et al, 2009;Liang et al, 2018). The 23 kDa form has two GR (Glu/Arg) repeats that work as Nuclear Localization Sequences (NLS), whereas the 17 kDa form has one.…”
Section: Introductionmentioning
confidence: 99%